Over a million students use our free study notes to help them with their homework
We use the form ax^2+bx+cTo factorise we need to put the equation into 2 bracketsThese 2 brackets will be in the form (x+k)(x+j) where k and j are to be foundWe need to find a combination of k and j for w...
f(x)=(12x^2)(e^2x) - 14, so using the chain rule f'(x)=(24x)(e^2x) + (12x^2)(2e^2x).To find the turning points set f'(x)=0, so (24x)(e^2x) + (24x^2)(e^2x) = 0. Thus (24xe^2x)(1+x)=0. Thus x=0 or x=-1.
Let's label the equations x2 + y2 = 25 (1) y - x = 1 (2). We can use substitution to solve this simultaneous equation. Let's make y the subject of the equation (2) and we get y = x...
To rationalise a surd means to manipulate a fraction involving terms which are being square rooted so that no term in the denominator is being square rooted. For this example 2/root(x) we multiply the fra...
Firstly, you need to get the equation to equal zero, so that you can use the quadratic formula to solve. Therefore you subtract 7 from both sides, meaning the equation becomes: 3x^2+7x-20=0. Recall the qu...
←
640
641
642
643
644
→
Internet Safety
Payment Security
Cyber
Essentials